Somatic Embryogenesis Induction in Coffea arabica L. by 2,4-Dichlorophenoxyacetic acid and 6-Furfurylaminopurine - Tarigan, Puji Lestari; Sukendah, Sukendah; Dewanti, Felicitas Deru; Pribadi, Nathasya Yusvie; Zulmi, Shinta Nuraini (Universitas Panji Sakti, 2024)
Coffee plants typically produce for 5 to 20 years before requiring rejuvenation to maintain sustainable production levels. Tissue culture methods offer a way to efficiently produce coffee seedlings with identical genetics on a large scale, while also protecting against pests and diseases. This research focuses on developing suitable culture media for generating coffee through somatic embryogenesis, as an initial stage in creating synthetic seeds. The coffee leaf explant from young leaves. The materials were MS media, alcohol 70%, 2,4-D, Kinetin, vitamin C, Dithane M-45, Agrept, and aquades. The culture used bottles, tweezers, autoclaves, hot plates, and LAF. The treatment was the concentration of 2,4-D and Kinetin. The treatments were: 1) D0K0=0 mL.L-1 2,4-D + 0 mL.L-1 Kinetin, 2) D1K0=2 mL.L-1 2,4-D + 0 mL.L-1 Kinetin, 3) D2K0=4 mL.L-1 2,4-D + 0 mL.L-1 Kinetin, 4) D0K1=0 mL.L-1 2,4-D + 2 mL.L-1 Kinetin, 5) D0K2=0 mL.L-1 2,4-D + 4 mL.L-1 Kinetin, 6) D1K1= 2 mL.L-1 2,4-D + 2 mL.L-1 Kinetin, 7) D2K2=4 mL.L-1 2,4-D + 4 mL.L-1 Kinetin, 8) D1K2=2 mL.L-1 2,4-D + 4 mL.L-1 Kinetin, and 9) D2K1=4 mL.L-1 2,4-D + 2 mL.L-1 Kinetin. Each treatment is replicated three times, so there are 27 experimental units. The treatment D1K1 results showed that the highest percentage of life calli induction was 74%, fastest callus induction times were at 25 days, then yellowish color and a crumbly texture were the most ideal morphological variables.